Psychosocial Care Center: daily work and articulation with the network in the pandemic - Aline Delmondes Silvano; Larissa de Almeida Rezio; Felipe Aureliano Martins; Marina Nolli Bittencourt; Mirelly Thaina de Oliveira Cebalho; Ana Karolina Lobo da Silva; Flavio Adriano Borges (Universidade Federal do Ceará, 2022)
Objective: to analyze the daily work of a Psychosocial Care Center and its articulation with the Psychosocial Care Network in the context of the COVID-19 pandemic. Methods: this is a qualitative study, produced by means of the researcher's diary and semi-structured interviews with nine health professionals, submitted to thematic-categorical content analysis. Results: the pandemic revealed failures in the management of services, lack of public investment, and the unpreparedness of professionals, intensifying work fragmentation, network disarticulation, non-assistance, and pre-existing asylum practices. Conclusion: the reality of the daily work of psychosocial care services shows that multifaceted actions that consider the complex social process of the psychiatric reform are necessary, especially in the pandemic, seeking the effective institutionalization of the psychosocial care model and the formation of centers of resistance to the established asylum model.